Defect structure in nanoalloys - Yacamán, Miguel José; Pérez Tijerina, Eduardo; Mejía Rosales, Sergio (Royal Society of Chemistry, 2007)
The defect structure of bimetallic nanoparticles differs from that of particles made of a single atomic species. Using high resolution TEM imaging along with molecular dynamics simulations, it is possible to investigate the nature and features of these defects. The definition of a local order parameter allows one to locate regions with different kinds of stacking on the simulated nanoparticles and thus to make a direct comparison with the experimental observations.